Thermal energy analysis of multi-walled carbon nanotubes Fe3O4/H2O flow over nonuniformed surface with Darcy–Forchheimer model - Lotfi, Chibani; Redouane, Fares; Zineb, Chikr Djaoutsi; Jamshed, Wasim; Eid, Mohamed R.; Ibrahim, Rabha W.; Mohamed Isa, Siti Suzilliana Putri; Alqahtani, Haifa; Hussain, Syed M. (SAGE Publications, 2023)
In this study, a new cavity shape was filled with an extension multi-walled carbon nanotubes-Fe2O3/H2O nanofluid under a constant magnetic field. The Darcy–Forchheimer model is used to account for the inertial impact of advection in the porous layer while maintaining the laminar and incompressible nature of the nanofluid flow. The dimensionless version of the governing equations is used to describe the issue and the finite element approach is used to resolve it. Through this complex geometry, various thermophysical factors such as Rayleigh number, Hartmann number, and nanoparticle concentration are considered. The porous layer's numerous characteristics are also explored. For example, its porosity and Darcy number, which indicates the permeability of the porous medium. The content of the hybrid nanofluid is considered to be Newtonian, stable, incompressible, and following a constant Prandtl number for the base fluid. Calculations are made according to the finite element method. The results of this work are presented in terms of rheology, isotherms, entropy generation, and mean Nusselt numbers. They have demonstrated that increasing the Rayleigh and Darcy numbers improve heat transfer in the enclosure.